Pengaruh Kecerdasan Intelektual (Intellectual Quotient) Dan Kecerdasan Emosional (Emotional Quotient) Terhadap Pembentukan Karakter Religius - Mohammad Arifin; Ainur Rofiq; Syahrul Ode Aliani (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2022)
The article aims to obtain the results of field studies on XI students at Madrasah Aliyah Negeri 1 Mojokerto about (1) the level of intellectual intelligence of students, (2) the level of emotional intelligence of students, (3) the level of the religious character of students, (4) the influence of intellectual intelligence on the formation of students' religious characters, (5) the effect of emotional intelligence on the formation of students' religious characters, and (6) the influence of both on the formation of students' religious characters. The type of research used is quantitative research with a regression approach. The research subjects were 50 respondents from 156 students using a questionnaire technique for variable data (X1) as IQ (Intellectual Quotient), variable (X2) as EQ (Emotional Quotient), and religious character as a variable (Y). The research data were analysed using the SPSS 22.0 application. They tested the research hypothesis using simple and multiple regression analysis. The results of the research on class XI students at MAN 1 Mojokerto showed that: (1) students' IQ levels were in a good category, (2) students' EQ levels were in a good category, (3) students' religious character was in a good category, (4) there was a significant influence, and the positive of IQ on the Religious Character of students is 73.2%, (5) There is a significant and positive effect of EQ on the Religious Character of students of 69.8%, and (6) Simultaneously both also have an effect of 71.5% on the religious character of students and has a very strong relationship quality.